2022
DOI: 10.1039/d1gc04584a
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic synthesis of α,α-gem-dihalide ketones from α-mono-halide ketones and unexpected dimer condensation

Abstract: A novel, environmentally-friendly method has been developed to prepare α,α-gem-dihalide (F, Cl, and Br) ketones from α-mono-halide ketones in an aqueous solution containing an alkali halide salt using an electrocatalytic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…7 shows the Stern–Volmer plot spectroscopy. 43 The electron transfer in the quenching process was analyzed using eqn (1):where I o is the luminescence intensity in the absence of a quencher, I f is the fluorescence intensity, and K sv represents the Stern–Volmer static quenching rate constant. The K sv was calculated as the slope of the Stern−Volmer lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 shows the Stern–Volmer plot spectroscopy. 43 The electron transfer in the quenching process was analyzed using eqn (1):where I o is the luminescence intensity in the absence of a quencher, I f is the fluorescence intensity, and K sv represents the Stern–Volmer static quenching rate constant. The K sv was calculated as the slope of the Stern−Volmer lines.…”
Section: Resultsmentioning
confidence: 99%
“…7 shows the Stern-Volmer plot spectroscopy. 43 The electron transfer in the quenching process was analyzed using eqn (1):…”
Section: Mechanism Experimentsmentioning
confidence: 99%
“…Phospholipid is an important component of cell membranes and is a basic structural unit for the formation of various biological tissues. , As shown in Figure A, a phospholipid is an amphiphilic molecule with hydrophobic lipid ends and hydrophilic phosphate or organic amine groups, and most importantly, the shellac monomer has a similar molecular structure (Figure S20). We hypothesized that perhaps it was this molecular similarity that allowed shellac monomer to easily penetrate cell membranes and promote wound healing, and therefore, the binding interactions between shellac and phospholipid were simulated and investigated. …”
Section: Resultsmentioning
confidence: 99%
“…The radical clock experiment showed that the vinyl cyclopropane derivative F achieved the rupture of the three-membered ring G , which was detected through HPLC-MS analysis (see the ESI† for details, Scheme 5e), which confirmed the existence of the chlorine radical during the reaction. 19 The fluorescent probe response test of ClO − showed that a trace amount of ClO − ( ca. 2.5 × 10 −4 mol L −1 ) was generated in the transformation (see the ESI† for details).…”
Section: Resultsmentioning
confidence: 99%